Pelatihan Incenerator Kepada Pekerja Untuk Mengurangi Limbah Produksi di Pabrik Tahu Sidoarjo - Mochamad Saleh; Bambang Triono; Moch Syaiful Anwar (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service aims to improve the ability of workers in operating incinerators in a tofu factory located in Sidoarjo. The background of this activity is the low understanding and skills of workers related to the operation of the equipment, especially in the aspects of operational procedures and work safety. The subject of this activity is the involvement of 10 workers in the production process. The method used is a participatory approach in the preparation stage, socialization or provision of materials, direct operational practice, and monitoring and evaluation. The training materials include an introduction to incinerators, the working principles of the equipment, Standard Operating Procedures (SOP) and Occupational Safety and Health (K3). The implementation of this activity resulted in a significant increase in the understanding and skills of participants, as indicated by an increase in the level of understanding from around 20% before the training to 80% after the training. In addition, there were positive changes in the work patterns of participants, such as increased awareness of the importance of safety and more responsible waste management. Thus, this activity has been proven to be able to improve the abilities of workers and support better waste management in the tofu factory.